PENGGUNAAN UTANG PADA SAAT FASE PERTUMBUHAN: “KEPUTUSAN REAKTIF ATAU KEPUTUSAN RASIONAL - Bayu Sindhu Raharja; Muji Mranani (Universitas Ahmad Dahlan, 2016)
The focus of this study is to test the effect of the company’s growth and thecompany’s performance. This research also tests whether the poor long-termperformance of high growth company caused by the manager overreaction behavior in using debt forfi nancing decisions. Debt policy decisions serve as a form of proxy decision-reactive managers in deciding the funding policy. The results of this study stated that the high growth companies have poor performance in the future. However, the poor performance in the future was not caused by reactive decision- making managers in using debt for fi nancing their business. This study shows the opposite, the policy of the use of debt actually positively impact the company’s performance in the future. Thus, the use of debt as a source of funding when the company is in a growth phase rational decisions.